‘Why should I trust you with my money?’: credible commitments in the informal economy in China - Varese, Federico (The British journal of criminology, 2019)
This article explores theoretical and empirical features of informal value transfer systems, the illegal transfer of money between jurisdictions. It identifies the trust relationships between the actors involved and discusses four mechanisms used to signal trustworthiness. It then applies these theoretical considerations to China, where transferring money abroad cannot exceed a limited amount, and the process is costly. While most authors stress the importance of trust, we find that informal mechanisms of credible commitments, such as reputation, repeated interaction, hostage taking and sharing compromising information, are used. These strategies underpin an industry that transfers billions of dollars out of China every year. We found no evidence of use of violence or Mafia involvement. The article is based on field research, interviews with bankers and customers, and a review of official documents and news reports in Chinese and English.